Efficacy of digital educational intervention using I-Change model in promoting preventive behaviors for cervical cancer among Iranian women: A randomized controlled trial - Sara Kazemi; Fatemeh Zarei; Alireza Hidarnia; Fatemeh Alhani (Health Promotion Perspectives)
Background: Cervical cancer (CC) is a major health concern for women, yet stigma and embarrassment often prevent preventive care. Digital health education offers a private, accessible way to learn about CC prevention. This study evaluated the effectiveness of a digital educational intervention based on the I-Change model in promoting preventive behaviors among Iranian women. Methods: A randomized controlled trial (RCT) was conducted with 210 women (18–49 years) from Ramsar, Iran. Participants were assigned to three groups: two intervention groups (mobile app and digital booklet) and a control group. The "Evaluation of Preventive Behaviors Against CC (PERCICA)" questionnaire assessed outcomes. The intervention included a pre-test, digital education, and follow-ups immediately and at 12 weeks post-intervention. Data were analyzed using t-tests, analysis of Variance (ANOVA), analysis of covariance (ANCOVA), and repeated measures ANOVA. Results: The app group showed significant improvements in knowledge, perceived risk, self-efficacy, cognitive barriers, and social support (P<0.05). Preventive behaviors (e.g., condom use, Pap tests, genital exams) were highest in the app group (67.12%, 95% CI: [29.32±2.35]), followed by the booklet group (38.57%, 95% CI: [9.55±2.17]). Conclusion: The app was more effective in sustaining behavioral changes and promoting CC prevention than the booklet, highlighting the value of tailored digital education for sensitive health topics. Trial Registration: ClinicalTrials.gov IRCT20181205041861N3. Registered V2.0 on 26 October 2021 with the IRCTID, V1.0. https://irct.behdasht.gov.ir/trial/57157.